A novel homozygous mutation in TRAPPC9 gene causing autosomal recessive non-syndromic intellectual disability - Mutaz Amin; Cedric Vignal; Esraa Eltaraifee; Inaam N. Mohammed; Ahlam A. A. Hamed; Maha A. Elseed; Arwa Babai; Iman Elbadi; Doua Mustafa; Rayan Abubaker; Mohamed Mustafa; Severine Drunat; et al. (BMC, 2022)
Abstract Background The etiology of intellectual disabilities is diverse and includes both genetic and environmental factors. The genetic causes of intellectual disabilities range from chromosomal aberrations to single gene disorders. The TRAPPC9 gene has been reported to cause autosomal recessive forms of intellectual disabilities in 56 patients from consanguineous and non-consanguineous families around the world. Methods We analyzed two siblings with intellectual disability, microcephaly and delayed motor and speech development from a consanguineous Sudanese family. Genomic DNA was screened for mutations using NGS panel (NextSeq500 Illumina) testing 173 microcephaly associated genes in the Molecular Genetics service in Robert Debre hospital in Paris, France. Results A novel homozygous mutation (NM_031466.7 (TRAPPC9):c.2288dup, p. (Val764Glyfs*7) in exon 14 of TRAPPC9 gene was found in the two patients. The mutation was predicted to cause nonsense mediated decay (NSMD) using SIFT prediction tool. The variant has not been found in either gnomAD or Exac databases. Both parents were heterozygous (carriers) to the mutation. Conclusion This is the first study to report patients with TRAPPC9-related disorder from Sub-Saharan Africa.